2003
DOI: 10.1046/j.1364-3703.2003.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential display analysis of gene expression in the cytoplasm of giant cells induced in tomato roots by Meloidogyne javanica

Abstract: SUMMARY Giant cells induced by root-knot nematodes are highly specialized cells which function as transfer cells and provide nutrients to support the growth and reproduction of the nematode. Changes in the overall pattern of gene expression in giant cells occur during the formation and maintenance of the nematode feeding cells. Differential display analysis has been carried out to detect changes in gene expression in giant cells induced in tomato roots by Meloidogyne javanica, using mRNA isolated directly from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 33 publications
2
25
0
1
Order By: Relevance
“…In addition, the interconnections suggested a possible role as a regulator for cysteine synthase whose amount at CE is correlated with several enzymes, glucose, and fruit diameter at OR. This enzyme has been suggested to play a key role in highly metabolically active cells (Wang et al , 2003). Those facts should be taken into account when trying to modify gene expression or protein contents in order to alter metabolite contents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the interconnections suggested a possible role as a regulator for cysteine synthase whose amount at CE is correlated with several enzymes, glucose, and fruit diameter at OR. This enzyme has been suggested to play a key role in highly metabolically active cells (Wang et al , 2003). Those facts should be taken into account when trying to modify gene expression or protein contents in order to alter metabolite contents.…”
Section: Discussionmentioning
confidence: 99%
“…Bar-Or et al , 2005; Jammes et al , 2005,). Nevertheless, though technically challenging, giant cell contents can be isolated using microaspiration (Wang et al , 2003) or laser-capture microdissection (LCM; Fosu-Nyarko et al , 2009; Barcala et al , 2010; Portillo et al , 2009, 2013). The research of Barcala et al (2010) and Portillo et al (2013) demonstrated the molecular distinctiveness between the giant cells and the surrounding gall tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Galls are voluminous and complex multicellular structures containing only five to eight GCs. The contribution of GCs to the gall is relatively small, particularly in the early stages of development (Wang et al, 2003). Microcapillar-aspired and hand-dissected tomato GCs contain GC-enriched material (Wilson et al, 1994;Wang et al, 2003 (Ithal et al, 2007b;Klink et al, 2007) and microaspiration in Arabidopsis (Szakasits et al, 2009).…”
Section: Down-regulation Of Gene Expression Occurs Early During Gc DImentioning
confidence: 99%
“…Microarray technologies have been applied mainly to whole galls containing GCs and the surrounding tissue (Bar-Or et al, 2005;Hammes et al, 2005;Jammes et al, 2005;Fuller et al, 2007). Wang et al (2003) attempted to overcome this limitation through microaspiration of GC contents, but this technique is limited to large GCs at late infection stages, when most of the gene re-programming events leading to cell differentiation are likely to have already occurred. The first microarray analysis from isolated GCs by laser capture microdissection (LCM) has been recently performed in tomato (Portillo et al, 2009), but not in Arabidopsis, which contains smaller root cells.…”
Section: Introductionmentioning
confidence: 99%